Political Bargaining and Judicial Intervention in Constitutional and Antitrust Federalism - Jim Rossi (Washington University Law Quarterly, 2005)
Federal judicial deference to state and local regulation is at the center of contentious debates regarding the implementation of competition policy. This Article invokes a political process bargaining framework to develop a principled approach for addressing the appropriate level of judicial intervention under the dormant commerce clause and state-action immunity from antitrust enforcement. Using illustrations from network industries, it is argued that, at core, these two independent doctrines share a common concern with political (not only market) failure by focusing on the incentives faced by powerful stakeholders in state and local lawmaking. More important, they share the common purpose of deterring the adoption of regulations with adverse spillover effects for those who do not participate in the relevant lawmaking process. The Article illustrates how a political process bargaining approach to these doctrines differs in its recommendations from traditional formulations, with implications for the degree of deference courts afford state and local laws.
Keywords: Antitrust law; Government liability – United States – States; Federal government; Political questions & amp; judicial power; Deregulation; Federalism; Interstate commerce; State action (Antitrust law); United States